Infographics and independent learning for English learning in the secondary level context - Fiorentina Dewantari; I Gusti Ayu Lokita Purnamika Utami; Made Hery Santosa (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2021)
Visual media are still ineffective in covering all learning focus and learning activities to support independent learning. Independent learning guides students to learn the material by themselves, but it is still not supported by the existing visual media. Infographics are a medium that underlies transformative skills in teaching because they can provide a complete learning focus in each material. This study was aimed at developing English teaching media for the 9th grade. A Design and Development research (DnD) proposed by Richey and Klein (2005) was used in this study, including design, development, and evaluation. Initial observations have been carried out at one of the junior high schools in Buleleng, Bali, Indonesia. Data collection was carried out by library research relating to the development of infographics and the nature of independent learning, document analysis by doing syllabus analysis, and expert judgment. The results obtained from the research are infographics are considered to be very good as a medium for teaching English for independent learning. This research implies that teachers' technology-based teaching skills can be assisted by developing this infographic teaching media.